Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 56249 species occurrences available in GBIF matching the query: { "or" : [ "DatasetKey is Collection Crustacea SMF", "DatasetKey is (Data S1) Palynology of IODP Hole 318-U1356A", "DatasetKey is Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea)", "DatasetKey is CSIRO, Australian National Algae Culture Collection (ANACC), Global, 1949-2008", "DatasetKey is Marine birds and mammals of the Southern Ocean (a census for the CAML)", "DatasetKey is Antarctic Porifera database from the Spanish benthic expeditions: Bentart, Gebrap and Ciemar", "DatasetKey is Colección de peces marinos del mar argentino y aguas adyacentes del INIDEP", "DatasetKey is RMT Trawl catch from the 1986/87 V7 AAMBER voyage", "DatasetKey is Biogeographic distribution of Antarctic and sub-Antarctic Mysida", "DatasetKey is Phytoplankton samples - 2005/06 V3 BROKE-West", "DatasetKey is Antarctic Krill occurrence data from Discovery expeditions", "DatasetKey is Distribution of surface phytoplankton between New Zealand and Antarctica, December 1957", "DatasetKey is Collection Echinodermata - ZMB", "DatasetKey is Nekton and plankton counts from RMT (320 µm) hauls of cruise GAE 1975/76", "DatasetKey is MNA - Sezione di Genova - (Marine Biological Samples)", "DatasetKey is Diatoms from the Vestfold Hills Lakes", "DatasetKey is Antarctic Krill occurrence data from Ukraine YUGNIRO Institute", "DatasetKey is (Table 12) Distribution of benthic foraminifera in bottom sediments of the Lazarev Sea", "DatasetKey is Marine palynomorph abundance estimates of sediment core CRP-2A (Fig. 2)", "DatasetKey is Antarctic Marine Protists species checklist", "DatasetKey is RMT Trawl catch from 1985/86 V1 ADBEX III voyage", "DatasetKey is (Appendix 1) Abundances of benthic forminifera in ODP Hole 113-689B", "DatasetKey is Nemertina World Checklist", "DatasetKey is Relative abundance of Quaternary foraminifera of sediment core CRP-1 (App. 1)", "DatasetKey is ANTXXIII-8 Birds and Mammals", "DatasetKey is Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1)", "DatasetKey is MNA (Section of Genoa) and NIWA Invertebrate Collection - Ross Sea Tanaidacea", "DatasetKey is Cetacean Sightings Survey and Southern Ocean Cetacean Program - BROKE-West", "DatasetKey is Squid specimens from the 1991/92 V6 AAMBER2 voyage", "DatasetKey is Collection Hydrozoa - ZMB", "DatasetKey is (Table 5) Distribution of calcareous nannofossils in the Paleocene of ODP Hole 113-690C", "DatasetKey is Table II: Birds observed at the Weddell Sea during the period: 22 December 1959 to 14 January 1960" ] } The dataset includes 56249 records from 32 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0098560-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences